Effects of fishmeal replacement by black soldier fly on growth performance, digestive enzyme activity, intestine morphology, intestinal flora and immune response of pearl gentian grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Huang, Bocheng; Zhang, Shuang; Dong, Xiaohui; Chi, Shuyan; Yang, Qihui; Liu, Hongyu; Tan, Beiping; Xie, Shiwei (Fish & shellfish immunology, 2022)
An 8-week feeding trial was conducted to investigate the influence of partial replacement of fishmeal (FM) by black soldier fly (BSF) (Hermetia illucens) on the growth, distal intestine morphology, intestinal flora, and intestinal immune response of pearl gentian grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂). Four diets were formulated, 0% (0 g kg−1), 10% (50 g kg−1), 20% (100 g kg−1) and 30% (150 g kg−1) fishmeal were replaced with BSF, named as FM, BSF10, BSF20, BSF30, severally. The study found that, with the increasing dietary BSF levels, growth and feed conversion ratio of fish decreased significantly (P < 0.05). Chitinase and trypsin activities were significantly increased with increasing dietary BSF levels (P < 0.05). With the increasing dietary BSF levels, distal intestinal muscularis thickness and mucosal fold length decreased significantly (P < 0.05), as well as total abundance of intestinal flora. The relative abundance of four phyla and six genera among the top 20 genera were significantly affected by dietary BSF levels (P < 0.05). With the increasing dietary BSF levels, the mRNA levels of nf-κbem1, r-cel and il-10 up-regulated significantly (P < 0.05). For fish fed BSF30 diet, the mRNA levels of myd88 and tlr22 were significantly higher than fish fed FM diet (P < 0.05). In conclusion, replacement fishmeal with BSF increased activity of digestive enzymes, but negatively affected growth performance and intestinal health of pearl gentian grouper. •The feasibility of replacing fishmeal with black soldier fly in pearl gentian grouper diet were investigated.•Dietary replacement of 10% fishmeal with BSF can negatively affected growth performance and intestinal health.•Dietary replacement of fishmeal with BSF increased feed intake and digestive enzymes activities.